Fluorinated trimethyllysine as a 19F NMR probe for trimethyllysine hydroxylase catalysis. Issue 6 (24th January 2017) - Vijayendar Reddy, Y.; Al Temimi, Abbas H. K.; Mecinović, Jasmin
Abstract : Human trimethyllysine hydroxylase (TMLH)-catalysed C-3 hydroxylation of N ε -(fluoromethyl)dimethyllysine can be monitored by 19 F NMR spectroscopy. Abstract : Trimethyllysine hydroxylase (TMLH) catalyses C-3 hydroxylation of N ε -trimethyllysine in the first step of carnitine biosynthesis in humans. Studies on TMLH have been hampered by the lack of established chemical methods. We report that an N ε -trimethyllysine analogue that contains the fluoromethyl group can be used as a 1 H and 19 F NMR probe for studies on TMLH catalysis.